IMPLEMENTASI METODE SWOT&QSPM (QUANTITATIVE STRATEGIC PLANNING MATRIX PADA ANALISA KEPUTUSAN INVESTASI KOMODITAS KELAPA (Cocos Nucifera L) DI KABUPATEN INDRAGIRI HILIR - Khairul ihwan; Yusriwarti; Roberta Zulfhi Surya (Indragiri Islamic University, 2022)
Investment activity is an activity that cannot be separated from decision analysis because investing requires an analysis of appropriate decision-making in order to minimize failure or maximize profits. Investing in coconut commodity business activities is a promising business for investors. However, to maximize profits on investment, proper analysis techniques are needed. In this study, the authors used the SWOT and QSPM methods in analyzing investment decisions in the coconut commodity business in Indragiri Hilir district. From the results of the investment decision analysis carried out, there are several important recommendations that can help coconut farmers and business actors be mutually beneficial, among other things: Increasing the promotion of buying and selling coconuts Innovating coconut trading businesses Increasing the capacity of business owners and their workforce through a series of government training and coachingIncreasing the frequency of transactions.